Frindle - Clements, Andrew, 1949-; Selznick, Brian (New York : Aladdin Paperbacks, 1998)
When he decides to turn his fifth-grade teacher's love of the dictionary around on her, clever Nick Allen invents a new word and begins a chain of events that quickly moves beyond his control.
AudioFile.
Booklist.
School Library Journal.
4.8
3-6
Keywords: Schools -- Juvenile fiction; Teacher-student relationships -- Juvenile fiction; Words, New -- Juvenile fiction; Schools -- Fiction; Teacher-student relationships -- Fiction; Words, New -- Fiction; New words -- Fiction; School stories; Teacher-student relationship -- Fiction